Necesidad de reformar el art. 57 de la Ley Orgánica del Sistema Nacional de Contratación Pública, para garantizar los principios de legalidad, transparencia, igualdad y trato justo en las contrataciones en situaciones de emergencia. - Torres Márquez, Mabel Mariana (2015)
Public procurement for emergencies in the country is a way to implement a special procedure in order to overcome the hazards presented. This work involves analysis of the mechanisms for entities to make possible this type of procedure and carry out the various recruitment processes that, without being outside the law, are exempt from such formalities and requirements. The rise of emerging situations that decision are made taking advantage of laws, decrees, statutes, regulations, resolutions to resolve the various joints. The proposed topic involves the study of one of the emergency, such as contracts in emergency situations, analyzed from a legal perspective in balance with the public interest. In addition, this work focuses on determining the importance of having in mind the principles of legality, transparency, equality and fair treatment, because in emergent situations, you cannot extend indefinitely the decision-making but, long enough and necessary to overcome the problem with the search and analysis of the most suitable to be used for the existence of an effective internal and external control